(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The banking sector is a prime mover for the development of any region. Maybe, it is global, regional, central or any commercial bank, the activities of all banks are connected to the development of individuals, families, society, through augmenting the development of commercial, entrepreneurial developments. Banks are the main lever for the success of developmental plans of government at different levels. In our study, we examined the role of banking institutions in implementing the development programs of the governments. To conduct the study, we selected the Jorhat District of Assam (India). By applying the comparative case analysis of banks operated under the jurisdiction of Jorhat District we wanted to evaluate the banks in implementing the development programs in the developmental blocks of the district under the ambit of the study.